Software protection : a case study on the development of economic law. - Correa, Carlos Maria (1990)
Agrues that US leadership in software production and trade has been determinant in the definition of the current prevailing pattern of software protection. The majority of developing countries that have established regulations on the matter have done it in response to and in order to satisfy the demands of foreign firms and governments, particularly the US, rather than to meet local requirements.